Scaffolding tertiary students’ writing in a genre-based writing intervention. - Kuiper, Cindy; Smit, Jantien; De Wachter, Lieve; Elen, Jan (Journal of Writing Research, 2017)
In recent years, embedding writing into subject teaching through genre-based writing instruction (GBWI) has been advocated in tertiary education. However, little is known about how this approach can be shaped and implemented in this context. In a design-based research study in Dutch higher professional education, we aimed to explore how GBWI can be used to scaffold students’ writing within the subject of Event Organization and to what extent students learned to use the typical features of the genre ‘event proposal’. A 5-week subject-specific writing intervention was designed and subsequently enacted by a subject lecturer in a first-year class involving 13 students. Using a coding scheme for interactional scaffolding strategies, five interaction fragments were analyzed against the background of designed scaffolding and learning goals. The fragments indicated that the interplay of designed scaffolding (instructional materials and activities) and interactional scaffolding (teacher-student interactions) promoted students’ writing performance over time. Comparison of students’ pre- and posttests by means of an analytic scoring scheme pointed to statistically significant growth in the use of typical genre features (d=1.41). Together, the results of this design-based research study indicate the potential of GBWI for scaffolding and promoting tertiary students’ writing.